Integrating English Language into legal studies at an Omani College : inspirations and aspirations / Ali S. M. Al-Issa - Al-Issa, Ali S. M. (ACRULeT, Faculty of Education & UiTM Press, 2012)
Ever since its establishment in 1997, the College of Law formerly known as the College of Sharia and Law at Sultan Qaboos University has been heavily criticized for the lack of English language skills of its graduates, who have either failed to impress their employers or struggled to find jobs related to the legal field which has had negative implications for the Omanization process. English language in Oman is the only official foreign language and a significant tool for achieving multiple uses and values. This triggered a strong call for change by Sultan Qaboos University (SQU) and the College of Law administration to integrate English language into various legal courses offered at the college. This article discusses the steps and decisions taken by the decision makers at SQU and the College of Law to introduce the necessary changes to cater for the needs of the job market to help contribute to the development of Oman's economy. The discussion may have implications for change in other similar contexts around the world.